Incorporating English Podcast as A Learning Source to Improve Students’ Speaking - Bakri, Nurfadila; Korompot, Chairil Anwar; Aeni, Nur (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research explores the effectiveness of using English podcasts to support the enhancement of speaking skills among eighth-grade students at SMP Negeri 1 Makassar, this study adopted a quantitative pre-experimental approach that involved conducting a pre-test., a treatment phase, and a post-test, with the participation of 44 students from class VIII.3. The results showed notable improvements in both vocabulary acquisition (N-Gain = 0.62) and grammar mastery (N-Gain = 0.51). Statistical analysis through paired sample t-tests confirmed that these improvements were significant (p < 0.05). These outcomes support prior research highlighting the benefits of podcasts in fostering engaging and interactive language learning. The study concludes that English podcasts offer valuable exposure to authentic language use, making them a powerful resource for developing speaking skills. It suggests that teachers integrate podcasts into their instructional methods to increase student motivation and language competence. It is suggested that future studies explore the lasting impacts and wider implementation of podcasts across various educational settings.